Comparative analysis of left atrial appendage closure efficacy and outcomes by CHA2DS2-VASc score group in patients with non-valvular atrial fibrillation - Zhao, Mingzhong; Zhao, Mengxi; Hou, Cody R.; Post, Felix; Herold, Nora; Walsleben, Jens; Yuan, Qingru; Meng, Zhaohui; Yu, Jiangtao (Frontiers in Cardiovascular Medicine, 2022)
Background: Higher CHA2DS2-VASc score is associated with an increased risk of adverse cardio-cerebrovascular events in patients with non-valvular atrial fibrillation (NVAF), regardless of oral anticoagulation (OAC) status. However, whether this association still exists in patients undergoing left atrial appendage closure (LAAC) is unknown. We evaluated the impact of CHA2DS2-VASc score on LAAC efficacy and outcomes. Methods: A total of 401 consecutive patients undergoing LAAC were included and divided into 3 groups based on CHA2DS2-VASc score (0-2, 3-4, and ≥5). Baseline characteristics, periprocedural complications, and long-term outcomes were collected and compared across all groups. Results: There were no significant differences in implantation success, periprocedural complications, and long-term outcomes across all score groups. Kaplan-Meier estimation showed that the cumulative ratio of freedom from all-cause mortality (P=0.146), cardiovascular mortality (P=0.519), and non-cardiovascular mortality (P=0.168) did not differ significantly by CHA2DS2-VASc score group. LAAC decreased the risks of thromboembolism and major bleeding, resulting in a relative risk reduction (RRR) of 82.4% (P<0.001) and 66.7% (P<0.001) compared with expected risks in the overall cohort, respectively. Subgroup analysis indicated that observed risks of thromboembolism and major bleeding were significantly lower than expected risks in score 3-4 and score ≥5 groups, respectively. The level of RRR for thromboembolism increased with CHA2DS2-VASc score (P<0.001 for trend), but did not for major bleeding (P=0.2729 for trend). Conclusions: Patients with higher CHA2DS2-VASc score did not experience worse outcomes, which may be partly attributed to more benefits provided by LAAC intervention in such patients compared to those with low score.